El derecho de autor ante los desafíos del desarrollo en el entorno digital y las comunicaciones en los momentos actuales - Antúnez Sánchez, Alcides F.; Figueredo Paneque, Olivia V.; Soler Pellicer, Yolanda (Nómadas. Critical Journal of Social and Juridical Science, 2013)
The work gathers a thematic algid axis in your |conceptualización| and execution for the beings and agents that it is related with the right side of author. 3 make a space traveled for the beginnings of the activity we. The man from your |surgimiento| has created and it is which always it has distinguished it, however the author and the artist during unknown centuries were not protected nor your creations neither until the past century in which developed to him fully the concepts of individuality, property, straight natural or human. The right side of author can be said that existed always, but was not legislated, but that in the ancient societies, it created for the authors are governed for the right side of common property,that is to say, that it could dispose of they as a thing, as any other well material. The protection to the authors is relatively young although from the more remote periods already existed a notion of literary property, this the last one cannot refuse it absolutely, if we keep in mind that in blunt existed true workshops of copyists that reproduced the works in manuscripts, by not knowing the right side of author in the current sense. The development of the digital environment and the communications in the current moments is vertiginous. They spring up new forms of expression and creation, new manners, pathes and media of reproduction and access. The process of |globalización| of markets and economies in which finds to him immersed the current thing¨society of the information¨ does more and more necessary the use of the computer science as instrument for the treatment of data and your transmission of a place to other.